2015
DOI: 10.1111/joss.12155
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Interactions between Cheese Aroma and Taste

Abstract: Cross-modal interactions between cheese aroma and cheese taste, and between aroma were investigated. Aroma was varied by four mixture types and three concentrations, all with a background cheese taste, with four aroma only controls. All cheese aroma samples were produced using 10 aroma compounds commonly found in cheese but at varying individual concentrations of compound. A panel of assessors (n 5 8) evaluated in triplicate the intensities of four flavor attributes; overall intensity of cheese, fruity cheese,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Isoamyl butyrate and ethyl hexanoate are the most represented esters in samples of ripened cheese obtained from the experimental group. These compounds are characterized by a low odor threshold and are generally associated with the sweet, fruity, and floral notes of surface-ripened cheese flavor (Niimi et al, 2015). Lactones tend to increase in CG samples during ripening, remaining almost unchanged in ZG cheese samples.…”
Section: Discussionmentioning
confidence: 99%
“…Isoamyl butyrate and ethyl hexanoate are the most represented esters in samples of ripened cheese obtained from the experimental group. These compounds are characterized by a low odor threshold and are generally associated with the sweet, fruity, and floral notes of surface-ripened cheese flavor (Niimi et al, 2015). Lactones tend to increase in CG samples during ripening, remaining almost unchanged in ZG cheese samples.…”
Section: Discussionmentioning
confidence: 99%
“…Esters have an interesting impact on the development of surface‐ripened cheese flavor, due to their sweet, fruity, and floral notes (Niimi et al., ; Urbach, ). Ethyl acetate, ethyl butanoate, ethyl hexanoate, and ethyl octanoate represent the major esters commonly identified in many varieties of surface‐ripened cheese (Table ).…”
Section: Dynamic Extractions – Purge and Trap Thermal Desorption Somentioning
confidence: 99%
“…The combination of volatile compounds and their interactions contributes primarily to the formation of aroma and taste, which together constitute cheese flavor (Niimi et al., ; Zehentbauer & Reineccius, ). Cheese flavor, in combination with the overall appearance of cheese and its texture, is decisive for consumer selection and preference (Drake & Delahunty, ; Kilcawley, ).…”
Section: Introductionmentioning
confidence: 99%
“…The combined lexicon consisted of 36 descriptors including definitions and references for cheese flavor, feeling factors, and fundamental tastes. The fundamental tastes such as sweet, salty, sour, and bitter are important because Niimi et al () showed in model cheese systems that the elimination of tastes resulted in a major reduction in flavor intensities regardless of the aromatics present. Because actual samples in the study were not provided to the panel during orientation, they were instructed to allow the possibility of adding new attributes during evaluation if needed.…”
Section: Methodsmentioning
confidence: 99%